Evaluation of locally isolated aquatic bacteria as nanofactories for green synthesis of iron oxide and silver nanoparticles - Jacob, Patricia Jayshree (2019)
The Malaysian tropical aquatic environment embodies a vast ecological system of immense biodiversity. Its largely untapped microbial population represent a rich bioresource that could be exploited for commercial applications replacing unsustainable conventional processes that require high investment and release toxic residues. Iron oxide nanoparticles (IONP) and silver nanoparticles (AgNP) have demonstrated tremendous potential in a variety of applications. Unfortunately, high investment costs, low yield and failure for effective scale-up using current protocols calls for alternative eco-friendly, cost-effective solutions. Green synthesis mechanisms using microorganisms as nanofactories offer a facile, sustainable and environment-friendly approach. Thus, the objectives underscored in this thesis was to isolate Malaysian aquatic bacteria with the ability for extracellular, aerobic generation of IONP and AgNP, to optimise synthesis parameters including temperature, precursor and biomass concentration using Response Surface Methodology (RSM) for maximum NP yield and potential throughput scale up and to explore the application potential of biosynthesized AgNP for antimicrobial activity and IONP as a nanoadsorbent for industrial dyes.